1988
DOI: 10.1002/anie.198815341
|View full text |Cite
|
Sign up to set email alerts
|

The SF5‐Unit as Steric Protecting Group; Synthesis and Structure of F5SCSF3

Abstract: The following experiment provides a clear decision in favor of 5@' [Eqn. (c)]: if 4a generates the isotopomer 5 a a 0 loss of both OHo and O D o will be observed in MSMS-experiments; should 6a @' be generated, then (provided the isomers are separated by considerable barriers) elimination of OD' would occur exclusively. The assumption of a barrier preventing the rapid equilibration 5a" + 6 a @ is justified: ab initio MO calculations[41 (UHF 6-3 IG*//6-31G* + ZPVE) indicate that 5 @' is 37.3 kcal/ mol more stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, its nonlinear nature is an argument against such a type of bonding, because triple bonds often present a linear geometry, particularly for sp-hybridized carbon atoms. The 19 F NMR spectra of 1 at low temperature endorsed the notion that all the fluorine atoms bound to sulfur are equivalent, [3] as well as those bound to carbon. This result suggested a free rotation of the CF 3 groups, and an equilibration of eventual differ-A C H T U N G T R E N N U N G ences in the SF bond lengths.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, its nonlinear nature is an argument against such a type of bonding, because triple bonds often present a linear geometry, particularly for sp-hybridized carbon atoms. The 19 F NMR spectra of 1 at low temperature endorsed the notion that all the fluorine atoms bound to sulfur are equivalent, [3] as well as those bound to carbon. This result suggested a free rotation of the CF 3 groups, and an equilibration of eventual differ-A C H T U N G T R E N N U N G ences in the SF bond lengths.…”
mentioning
confidence: 82%
“…This molecule was prepared by cleaving HF from CF 3 CH=SF 4 or CF 5 CH 2 =SF 5 . [2][3][4][5][6] Four years later, the same group showed that F 5 SCSF 3 (2) can be isolated. Soon after the synthesis of these two intriguing molecules, several experimental [3][4][5][6] and theoretical [7,8] investigations were carried out to understand the nature of the carbon-sulfur triple bond.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations